Deep water acoustic calibration facility: Development of a platform - Malan, J.; Marouchos, A.; Sherlock, M.; Ryan, T.; Kloser, Rudy (2016)
© 2016 IEEE.Acoustic systems are used widely to provide quantitative estimates of biomass for fisheries and ecosystem assessments. Traditionally, these systems are attached to surface vessels, but increasingly they are being fitted to remote operated vehicles, autonomous vehicles and towed platforms. These platforms allow the acoustic transducer to get closer to targets, and provide increased resolution and, if calibrated, better accuracy of surveys at depth. To achieve better accuracy requires regular and methodical calibration of acoustic transducers at depth using calibration targets of a known acoustic signature. Standard methods exist for calibrating such systems just below the surface, but calibrating such systems at their operating depths is far more difficult. A bespoke system was necessary to allow scientists and technicians to calibrate acoustic transducers at their operating depths to quantify their characteristics and performance. This paper will discuss the design, development and testing of a DEepwater CAlibration Facility (DECAF). The design challenges are presented along with a discussion of difficulties in the operation of such a system.